PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA KEUNIKAN DAERAH TEMPAT TINGGALKU - Melinda Tri Ananda; Tatang Muhajang; Dendy Saeful Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Melinda Tri Ananda. 037118058. The Effect of Applying the Problem Based Learning Model on Learning Outcomes in the Uniqueness of the Area Where I Live. Elementary School Teacher Education Study Program Thesis. Faculty of Teacher Training and Education. Pakuan University. Bogor. 2022. This research is a quasi-experimental research. This study aims to determine the effect of applying the Problem Based Learning model to the learning outcomes of the sub-theme of the uniqueness of the area where I live in class IV. This research was conducted at Pasir Eurih 05 Public Elementary School, Bogor Regency, grades IV-A and IV-B from February to May, even semester of the 2021/2022 school year. The N-Gain calculation for the Problem Based Learning model is 68 with moderate criteria and the N-Gain value for the conventional model is 39 with moderate criteria. So that the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the conventional model.Researchers also carried out a normality test with the Liliefors test for both samples with normal distribution. Furthermore, in the hypothesis test, the tcount is 6.14406 greater than the ttable of 1.99714 indicating that Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the research above, it can be stated that there is an effect of applying the Problem Based Learning model to the learning outcomes of the sub-theme of the uniqueness of the area where I live in class IV at SD Negeri Pasir Eurih 05, Bogor Regency.